Complete Sequence of a blaNDM-1-Harboring Plasmid in an Acinetobacter bereziniae Clinical Strain Isolated in Argentina - Brovedan, Marco Alcides (2015)
The New Delhi metallo-β-lactamase (NDM-1) was initially identified in clinical isolates of Escherichia coli and Klebsiella pneumoniae in Sweden from a patient previously hospitalized in India (1). Since then, blaNDM-1 has frequently been reported in Enterobacteriaceae and Acinetobacter spp., with a fast dissemination in the Indian subcontinent, the Balkan countries, China, and the Middle East (2). NDM-1 producers generally associated with Enterobacteriaceae species have also been reported, albeit with much lower frequency, in Latin American countries, including Guatemala, Mexico, Colombia, and Brazil (3). Moreover, production of NDM-1 in this geographic region has also been noted in Acinetobacter baumannii in Honduras and Brazil (3, 4) and in Acinetobacter pittii in Paraguay and Brazil (5, 6). Here, we report the first case of an NDM-1-producing Acinetobacter species in Argentina, an Acinetobacter bereziniae clinical isolate. We describe also the complete sequence of a blaNDM-1-containing plasmid in this strain.